Оптимальне керування залежною від температури моделлю процесу ферментації - Matsyong, Ya. Ye.; Savula, Ya. H.; Shcherbatyi, M. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A mathematical model of must fermentation taking into account the dependence of model parameters on temperature is considered. An analytic form of this dependence (exponential and linear) is determined. The problems of parameter identification and optimal control are described. The numerical results for the problem of optimal control (the speed problem) and identification of parameters of the Rkatsiteli wine must fermentation are presented.